Genome-wide CRISPR/Cas9 screening for drug resistance in tumors - Zhang, Zhongyan; Wang, Hailiang; Yan, Qian; Cui, Jinwei; Chen, Yubin; Ruan, Shiye; Yang, Jiayu; Wu, Zelong; Han, Mingqian; Huang, Shanzhou; Zhou, Qi; Zhang, Chuanzhao; et al. (Frontiers in Pharmacology, 2023)
Genome-wide clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR associated nuclease 9 (Cas9) screening is a simple screening method for locating loci under specific conditions, and it has been utilized in tumor drug resistance research for finding potential drug resistance-associated genes. This screening strategy has significant implications for further treatment of malignancies that acquired drug resistance. In recent years, studies involving genome-wide CRISPR/Cas9 screening have gradually increased. Here we review the recent application of genomewide CRISPR/Cas9 screening for drug resistance, involving Mitogen-Activated Protein Kinase (MAPK) pathway inhibitors, Poly (ADP-ribose) polymerase inhibitors (PARPi), alkylating agents, mitotic inhibitors, antimetabolites, immune checkpoint inhibitors (ICIs), and cyclin-dependent kinase inhibitors (CDKI). We summarize the drug resistance pathways like the KEAP1/Nrf2 pathway MAPK pathway, NF-κB pathway, and so on. Also, we analyze the limitations and conditions for the application of genome-wide CRISPR/Cas9 screening techniques.